Breaking the myths (or how to have a successful career in science). (29th October 2018) - Ovenden, Jennifer R; ,
Abstract: The article is a recollection of the ups and downs of my career as a research scientist. It does not chronicle my career in the standard way; there is no timeline of events and only a few details of the type of research that I have devoted my life to. I feel the take-home messages are relevant no matter what type of science you do. The narrative jumps around between periods of my life, uses anecdotes freely and attempts to be informative, forthright, and entertaining. Although science is perceived as a profession, the career pathway can be uneven and forked. In addition to discipline-specific knowledge and experience, successful scientists need a multitude of skills; for instance, human management, logistics, and social media—to name a few. The field often attracts talented introverts for whom working in teams is challenging. The complexity of science is fascinating and powerful. In the fervour for discoveries, care is needed not to become isolated from friends and family by long working hours. For those of you who have gone part or full way down this path, there will be value in comparing your experiences to mine. Mostly I hope that younger scientists who are beginning on this path, or considering whether to enter, will take away some messages that will help them stand on our shoulders.